Closed reduction and drainage incision for the treatment of neglected and infected mandibular fractures - Hermanto, Eddy; Laihad, Fanny Margaretha; Pranoto, Amelia Elizabeth; Elidasari, Monika; Tantra, Ivan; Sarianoferni; Damayanti, Dian Widya (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Jaw fracture is the most common facial fracture in oral and maxillofacial bone and is usually caused by trauma. The fracture itself could lead to infection due to bone and tissue damage, which is the port of entry for microorganisms. Fracture-related infection (FRI) in the patient discussed in this study manifested as a submandibular abscess. The goals of fracture treatment were achieving the anatomic reduction of the fracture line and regaining acceptable occlusion. There are two methods for treating mandibular fractures: the closed method, also called conservative treatment, and the open method, which requires advanced surgery. Closed method treatment uses a maxillomandibular fixation (MMF) device in order to reduce and immobilize fracture fragments. Treatment of FRI should use a multidisciplinary approach to achieve an outstanding result, such as wound debridement, antimicrobial therapy, and implant retention. Purpose: The purpose of this article is to report a case of neglected mandibular fracture with a submandibular abscess, which was treated with a combination of the closed reduction method and incision drainage. Case: A 25-year-old female visited Nala Husada Hospital because of a submandibular abscess on the neglected mandibular fracture of the right parasymphysis and left corpus. Case management: The case was managed using an arch bar in the mandible and an eyelet in the maxilla while continuing with MMF and an extra oral drainage incision. Conclusion: Combination therapy (MMF and incision drainage) was needed to treat this case because of the occurrence of a submandibular abscess due to a neglected mandibular fracture.